Efeito da irradiação transcutânea sob artéria radial em variáveis hemodinâmicas de pacientes hipertensos: estudo clínico, randomizado e duplo cego - Isabella, Adriana Paula Jordão (2020)
Systemic Arterial Hypertension (SAH) os a multifactoril clinical condition, with a high rate of morbidity and mortality and low control rates. Althoough photobiomodulation (FBM) is able to induce a photobiological interaction inside cells and modify the micro and macrovascular response in situ, there is a lack of studies that demonstrate its systemic effect, mainly clinical and placebo controlled. Thus, this study aimed to evaluate the modulatory effects on the control of blood pressure in hypertensive patients after trancutaneous photobiomodulation of the radial artery. For this, 44 participants were randomly divided into 4 groups, onde group being irradiated for 60 minutes daily for 5 days, being repeated after 20 days with a total of 3 cycles (Group A), and their respective placebo (Group B); the third group was irradiated for 30 minutes daily, for 10 days, being repeated after 20 days, also totaling 3 cycles (Group C), and their respective placebo (Group D). All participants continued with conventional drug treatment previously instituted. Before the interventions, after each cycle anda t the end of them, blood pressure and heart ratewuere measured. Before and at the end of the interventions, blood samples were collectes to measure interleukins 6 and 1 beta. Statistical analysis was performed to compare the groups at each treatment stage, with α = 0,05. Modulatory effects have been shown to control blood pressure in hypertensive patients after photobiomodulation. Group A showed a better response to decrease hemodynamic variables tham group C. Group A showed less expression. Of interleukins IL - 1β and IL-6 compared to group C. Multidisciplinary care may have increased adherence to treatment for all participants, includin placebo groups, wich also showed a decrease in the values of hemodynamic variables.